Effects of Trioctyl Phosphate and Cresyl Diphenyl Phosphate as flame-retarding additives for Li-Ion battery electrolytes - Shim, Eun-Gi; Nam, Tae-Heum; Kim, Jung-Gu; Kim, Hyun-Soo; Moon, Seong-In (Metals and materials international, 2009)
Safety concerns related to lithium-ion batteries have been the key obstacle to their application in hybrid electric vehicles. Trioctyl Phosphate (TOP) and Cresyl Diphenyl Phosphate (CDP) were studied as potential flame-retarding additives for lithium-ion batteries. The electrochemical performance and thermal stability of the additive-containing electrolytes, in combination with a cell comprising a LiCoO 2 cathode and Mesocarbon Microbeads (MCMB) anode, were tested in coin cells. Cyclic Voltammetry (CV), Differential Scanning Calorimetry (DSC), Electrochemical Impedance Spectroscopy (EIS), and Scanning Electron Microscopy (SEM) were used for the experimental analysis. The study results revealed that CDP addition at 5 wt.% improved the cell stability due to the lower rate of the charge-transfer resistance increase over 30–50 cycles. CDP was demonstrated to be a better flame-retarding additive than TOP.